Activities on Using Social Media for Branding in E-Commerce - PhD. Nguyen Thi Thu Trang; Nguyen Thanh Nam; Nguyen Ngoc Thu Ngan; Vo Le Mai Huong; Le Ho Thao Nhi; Ngo Nhu Ngoc (Engineering And Technology Journal, 2024)
In the context of e-commerce, social media plays an important role in building a brand. This article presents the theory of social media and branding in e-commerce, emphasizing how businesses can optimize their communication strategies to enhance brand value. Specifically, the article analyzes methods such as search engine optimization (SEO), social media marketing, influencer marketing, and affiliate marketing. At the same time, to have a more objective view, the current situation of using communication in brand building in Vietnam is assessed through leading companies in the industry, in terms of their communication strategies, business results and market share. The article also points out the challenges and limitations that businesses face in applying social media. Finally, effective solutions are proposed to improve the ability to use communication to build brands in e-commerce in Vietnam. In general, the article not only provides an overview of theory and practice, but also proposes specific directions to help businesses develop sustainably in a fiercely competitive environment.